Basic of Fault Tree (FT) Method - Jasrin, Nurin Saqinah; Siti Amira Othman,; Nor Azman, Nor Farah Amirah; Abu Bakar, Nurul Fathihah (Enhanced Knowledge in Sciences and Technology, 2021)
A fault tree described the logical relationship between events and causes. This method shows significant success in analyzing the root cause of accident.  There are a lot of accidents due to human errors and equipment errors. This paper will reviewed the various accident occurrence that analysed by using Fault Tree (FT) method.